The Galling Truth: Limited Knowledge of Gall-Associated Volatiles in Multitrophic Interactions - Borges, Renee M. (Frontiers in Plant Science, 2018)
Galls are the product of enclosed internal herbivory where the gall maker induces a plant structure within which the herbivores complete their development. For successful sustained herbivory, gall makers must 1) suppress the induction of plant defences in response to herbivory that is usually mediated through the jasmonic acid pathway and involves volatile organic compound (VOC) production, or 2) have mechanisms to cope with herbivory- induced VOCs, or 3) manipulate production of VOCs to their own advantage. Similarly, plants may have mechanisms 1) to avoid VOC suppression or 2) to attract galler enemies such as parasitoids. While research on VOCs involved in plant–herbivore–parasitoid/predator interactions is extensive, this has largely focussed on the impact of piercing, sucking, and chewing external herbivores or their eggs on VOC emissions. Despite the importance of gallers, owing to their damage to many economically valuable plants, the role of volatiles in gall-associated herbivory has been neglected; exceptions include studies on beneficial gallers and their enemies such as those that occur in brood-site pollination mutualisms. This is possibly the consequence of the difficulties inherent with studying internally-occurring herbivory. This review examines the evidence for VOCs in galler attraction to host plants, potential VOC suppression by gallers, increased emission from galls and neighbouring tissues, attraction of galler enemies, and the role of galler symbionts in VOC production. It suggests a research focus and ways in which studies on galler-associated VOCs can progress from a philatelic approach involving VOC listing towards a more predictive and evolutionary perspective.